Ammonium polyphosphate microcapsule flame retardant

The surface of ammonium polyphosphate is coated with a polymer containing silicon boron atoms through an emulsion polymerization method, which solves the problem of poor safety and environmental protection in the preparation process of ammonium polyphosphate microcapsule flame retardant in the existing technology, and achieves good thermal stability and Water resistance and reduced production costs.

CN119350716APending Publication Date: 2025-01-24郑州轻大产业技术研究院有限公司 +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411665941.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, when preparing ammonium polyphosphate microcapsule flame retardant, there are problems such as poor safety and environmental protection, difficult production process, high production cost, and uneven surface coating of ammonium polyphosphate particles.

Method used

The emulsion polymerization method is used to coat the surface of ammonium polyphosphate with polymers containing silicon-oxyboron atoms. The reaction is carried out in aqueous solution and room temperature, avoiding the use of organic solvents, simplifying the process, and improving safety and environmental protection.

Benefits of technology

The good thermal stability, water resistance, and good compatibility of the ammonium micro -capsule luster of ammonium phosphate, and the good compatibility of water resistance and the substrate, reducing production costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350716A_ABST
    Figure CN119350716A_ABST
Patent Text Reader

Abstract

The invention relates to an ammonium polyphosphate microcapsule flame retardant, and belongs to the technical field of flame retardant materials. The ammonium polyphosphate microcapsule flame retardant is prepared by a method comprising the following steps: carrying out emulsion polymerization reaction on ammonium polyphosphate, an alkenyl silane coupling agent and a borosilicate polymeric monomer under the action of an organosiloxane / persulfate redox system containing Si-N bonds; the borosilicate polymeric monomer is prepared by carrying out condensation reaction on alkenyl trialkoxy silane and boric acid, and the mass ratio of the alkenyl trialkoxy silane to the boric acid is (14-15): (6-7). The ammonium polyphosphate microcapsule flame retardant disclosed by the invention does not need an organic solvent during preparation, and is simple in operation process, low in toxicity, convenient to produce, easy to control, safe and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ammonium polyphosphate microcapsule flame retardant, belonging to the technical field of flame retardant materials. Background Art

[0002] Ammonium polyphosphate is a halogen-free flame retardant. Its working principle is mainly to promote the formation of a carbonized layer in the material at high temperature, thereby effectively isolating oxygen, reducing heat transfer and preventing the spread of combustion. However, ammonium polyphosphate has the disadvantages of strong hygroscopicity, poor thermal stability, difficult processing and poor compatibility. However, these shortcomings can be overcome to a certain extent by improving the production process, surface modification and compounding. However, the water solubility of ammonium polyphosphate and its poor compatibility in polymers limit the application of ammonium polyphosphate. The traditional surface modification method of ammonium polyphosphate has little effect on improving the flame retardant efficiency. The method of compounding ammonium polyphosphate into a carbonizing agent / synergist is also not conducive to improving its flame retardant properties, mainly because it is difficult for ammonium polyphosphate and the carbonizing agent / synergist in the flame retardant system to be uniformly contacted by blending, especially the small molecule carbonizing agent has the problem of easy migration and difficult dispersion, and will cause great damage to the mechanical properties of the polymer material, and is not conducive to improving the flame retardant properties.

[0003] Coating is one of the most effective methods to change the surface properties of fillers by forming a layer of attached shell, which can improve the flame retardant properties, mechanical properties and water resistance of some polymer composites. The existing technology for coating ammonium polyphosphate is mainly microcapsule coating. The use of microencapsulation technology to coat ammonium polyphosphate can give ammonium polyphosphate good water resistance, improve its compatibility with the polymer matrix, and expand the application range of ammonium polyphosphate. At present, the method for microencapsulation of ammonium polyphosphate is mainly chemical coating, that is, the monomer corresponding to the capsule material undergoes polymerization reaction, and the capsule core is added during the reaction process, so that the capsule material generated by the reaction is coated on the surface of the flame retardant. This method has a good coating effect, but it has certain limitations. The reasons are: (1) The polymerization reaction needs to be controlled during the coating process, and the reaction conditions and by-products have a great influence on the coating quality, and it is not easy to form a product with stable quality; (2) There are multiple components such as monomers, prepolymers, by-products, etc. in the reaction system, which have a certain influence on the purity of the prepared flame retardant microcapsules.

[0004] Ran et al. disclosed in the article "Improving the flame retardancy and water resistance of polylactic acid by introducing polyborosiloxane microencapsulated ammonium polyphosphate" a polyammonium polyphosphate microcapsule flame retardant prepared by in-situ polymerization, wherein the preparation method specifically comprises the following steps: adding a mixture of 40 g polyammonium polyphosphate (APP), 1 g OP-10 and 60 mL diethylene glycol dimethyl ether to a three-necked flask equipped with a mechanical stirrer, adjusting the solution to a pH of 1 to 3 with hydrochloric acid, and stirring at 70°C for 30 min. 8.0 g PTMOS (phenyl trimethoxysilane) or a mixture of 6.9 g PTMOS and 1.1 g boric acid is added dropwise to a three-necked flask, then heated to 130°C and reacted for 5 h. Afterwards, diethylene glycol dimethyl ether and by-product methanol are evaporated by a rotary evaporator. Finally, the mixture is dried at 80°C for 24 h in a vacuum drying oven to obtain polyammonium polyphosphate microcapsule flame retardant Si-APP or BSi-APP. The prepared ammonium polyphosphate microcapsule flame retardant is introduced into polylactic acid (PLA), which can simultaneously improve the flame retardancy, water resistance and mechanical properties of the polylactic acid composite material.

[0005] However, the current in-situ polymerization method for preparing ammonium polyphosphate microcapsule flame retardants requires the use of a large amount of highly toxic organic solvents, the preparation process is not safe and environmentally friendly, and the production process is difficult to control, the preparation cost is high, and the polymer coating on the surface of the ammonium polyphosphate particles is uneven. Summary of the invention

[0006] The purpose of the present invention is to provide an ammonium polyphosphate microcapsule flame retardant, which can solve the problem of poor safety and environmental protection in the preparation process when the ammonium polyphosphate microcapsule flame retardant is currently prepared by an in-situ polymerization method.

[0007] In order to achieve the above purpose, the technical solution adopted by the ammonium polyphosphate microcapsule flame retardant of the present invention is:

[0008] An ammonium polyphosphate microcapsule flame retardant is prepared by a method comprising the following steps: subjecting ammonium polyphosphate, an alkenyl silane coupling agent and a borosilicate polymerization monomer to an emulsion polymerization reaction under the action of an organosiloxane containing a Si-N bond / persulfate redox system; the borosilicate polymerization monomer is prepared by a condensation reaction of an alkenyl trialkoxysilane and boric acid, wherein the mass ratio of the alkenyl trialkoxysilane to the boric acid is (14-15):(6-7); the structure of the organosiloxane containing a Si-N bond is as shown in Formula I;

[0009]

[0010] In formula I, R is methyl or ethyl.

[0011] The ammonium polyphosphate microcapsule flame retardant of the present invention is prepared by coating a polymer containing silicon oxygen boron atoms on the surface of ammonium polyphosphate by an emulsion polymerization method, and the organic siloxane containing Si-N bonds and persulfate constitute a redox initiator, so that the coating can be carried out under aqueous solution and room temperature conditions. The ammonium polyphosphate microcapsule flame retardant of the present invention does not require an organic solvent during preparation, has a simple operation process, low toxicity, convenient production and easy control, and is safe and environmentally friendly. The ammonium polyphosphate microcapsule flame retardant of the present invention has good thermal stability, water resistance, dispersibility during processing and use, and has good compatibility with the substrate.

[0012] Preferably, the alkenyl silane coupling agent is γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane or vinyltrimethoxysilane.

[0013] Preferably, the ratio of the mass of ammonium polyphosphate, the mass of the alkenyl silane coupling agent and the mass of the borosilicate polymerization monomer calculated as boric acid is (6-10):(6-8):(1.2-1.8).

[0014] Preferably, a catalyst is also added into the emulsion polymerization reaction, and the catalyst is calcium chloride and / or lithium chloride.

[0015] Preferably, the preparation method of borosilicate polymerization monomer is as follows: alkenyltrialkoxysilane, boric acid, water and ethanol are mixed to obtain a mixed solution, the pH of the mixed solution is adjusted to 3-4, the mixing reaction is carried out for 10-14 hours, and then the temperature is increased to 75-95°C, and the mixing reaction is continued for 5-9 hours to obtain a borosilicate polymerization monomer solution.

[0016] Preferably, the emulsion polymerization method comprises the following steps: mixing ammonium polyphosphate, an emulsifier and water to obtain an emulsion; then adding an alkenyl silane coupling agent, a borosilicate polymerization monomer solution, a redox system and a catalyst to the emulsion for a mixing reaction; or mixing ammonium polyphosphate, an alkenyl silane coupling agent, an emulsifier and water to obtain an emulsion; then adding a borosilicate polymerization monomer solution, a redox system and a catalyst to the emulsion for a mixing reaction; the catalyst is calcium chloride and / or lithium chloride.

[0017] Preferably, the mass ratio of ammonium polyphosphate, alkenyl silane coupling agent, borosilicate polymerization monomer solution, redox system and catalyst is (6-10):(6-8):(45-55):(2-5.4):(0.1-0.6).

[0018] Preferably, the mass ratio of ammonium polyphosphate, emulsifier and water is (6-10):(0.5-1.5):(55-75).

[0019] Preferably, the mass ratio of the organosiloxane containing Si-N bonds to the persulfate is (1.0-3):(0.1-0.4); the persulfate is ammonium persulfate, potassium persulfate or sodium persulfate.

[0020] Preferably, the mass ratio of ammonium polyphosphate, alkenyl silane coupling agent, borosilicate polymerization monomer solution, redox system and catalyst is (6-10):(6-8):(45-55):(2-3.2):(0.1-0.6); the mass ratio of organosiloxane containing Si-N bonds and persulfate is (1.5-3):(0.1-0.3). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a diagram of the operation process during emulsification in Example 1;

[0022] Figure 2 This is a schematic diagram of the appearance of the ammonium polyphosphate microcapsule flame retardant of Example 1;

[0023] Figure 3 The SEM electron microscope images of ammonium polyphosphate and the ammonium polyphosphate microcapsule flame retardant of Example 1;

[0024] Figure 4 It is the infrared test image of ammonium polyphosphate and the ammonium polyphosphate microcapsule flame retardant of Example 1;

[0025] Figure 5 It is a schematic diagram of the water contact angle test results of ammonium polyphosphate and the ammonium polyphosphate microcapsule flame retardant of Example 1;

[0026] Figure 6 This is a picture of the combustion test of silicone rubber prepared using the ammonium polyphosphate microcapsule flame retardant of Example 1;

[0027] Figure 7 This is a combustion test picture of polylactic acid prepared using the ammonium polyphosphate microcapsule flame retardant of Example 1. DETAILED DESCRIPTION

[0028] The ammonium polyphosphate microcapsule flame retardant of the present invention is a pioneering invention. The present invention adopts an emulsion polymerization method to coat a polymer containing silicon oxygen boron atoms on the surface of ammonium polyphosphate. The reaction can be carried out at room temperature, and the operation is simple, the toxicity is low, the production is convenient and easy to control. The coated polymer containing silicon oxygen boron atoms effectively improves the thermal stability of ammonium polyphosphate and the compatibility with the substrate, and reduces the problems of uneven dispersion and performance degradation caused by moisture absorption that may occur during processing and use.

[0029] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0030] Example 1

[0031] The ammonium polyphosphate microcapsule flame retardant of this embodiment is prepared by a method comprising the following steps:

[0032] (1) 6.0 g of boric acid, 14.0 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and placed in a 30° C. water bath. The pH of the material in the flask was then adjusted to 3 with glacial acetic acid. The material in the flask was stirred for 10 h. The material in the flask was then heated to 75° C., and a condenser was added and stirred for 5 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0033] (2) 6.0 g of ammonium polyphosphate, 0.5 g of emulsifier OP-20, 6.0 g of γ-methacryloxypropyltrimethoxysilane and 55.0 g of distilled water were added to a beaker and emulsified in an emulsifier for 30 seconds to obtain emulsion B. The operation process during emulsification is as follows: Figure 1 shown.

[0034] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.05 g of ammonium persulfate and 0.06 g of calcium chloride were added under stirring, and 2 g of distilled water and 1.5 g of organosiloxane containing Si-N bonds were quickly added dropwise. After stirring for 20 min, 45.0 g of solution A obtained in step (1) was added dropwise to the three-necked round-bottom flask, and then 0.05 g of ammonium persulfate, 0.06 g of calcium chloride, 2 g of distilled water and 0.5 g of organosiloxane containing Si-N bonds were added to the three-necked round-bottom flask. After stirring for 40 min, solution C was obtained. The structure of the organosiloxane containing Si-N bonds is as follows:

[0035]

[0036] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant, such as Figure 2 shown.

[0037] In this embodiment, when preparing ammonium polyphosphate microcapsule flame retardant, the chemical reaction occurring in step (1) is as follows:

[0038]

[0039] The chemical reaction occurring in step (3) is as follows:

[0040]

[0041] Example 2

[0042] The ammonium polyphosphate microcapsule flame retardant of the present embodiment is prepared by a method comprising the following steps:

[0043] (1) 6.0 g of boric acid, 14.0 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and placed in a 30° C. water bath. The pH of the material in the flask was then adjusted to 4 with glacial acetic acid. The material in the flask was stirred for 14 h. The material in the flask was then heated to 95° C., and a condenser was added and stirred for 9 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0044] (2) 10.0 g of ammonium polyphosphate, 1.5 g of emulsifier OP-20, 8 g of γ-acryloxypropyltriethoxysilane and 75 g of distilled water were added to a beaker and emulsified in an emulsifier for 120 s to obtain emulsion B.

[0045] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.1 g of ammonium persulfate and 0.06 g of calcium chloride were added under stirring, and 2 g of distilled water and 1.5 g of organosiloxane containing Si-N bonds were quickly added dropwise. After stirring for 20 min, 55 g of solution A obtained in step (1) was added dropwise to the three-necked round-bottom flask, and then 0.2 g of ammonium persulfate, 0.06 g of lithium chloride, 2 g of distilled water and 1.25 g of organosiloxane containing Si-N bonds were added to the three-necked round-bottom flask. After stirring for 40 min, solution C was obtained. The structure of the organosiloxane containing Si-N bonds is as follows:

[0046]

[0047] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant.

[0048] Example 3

[0049] The ammonium polyphosphate microcapsule flame retardant of the present embodiment is prepared by a method comprising the following steps:

[0050] (1) 7.0 g of boric acid, 15.0 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and the flask was placed in a 30° C. water bath. The pH of the contents in the flask was then adjusted to 4 with glacial acetic acid. The contents in the flask were stirred for 10 h. The contents in the flask were then heated to 75° C., and a condenser was added and stirred for 5 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0051] (2) 6.0 g of ammonium polyphosphate, 0.5 g of emulsifier OP-20, 6.0 g of γ-acryloxypropyltrimethoxysilane and 55 g of distilled water were added to a beaker and emulsified in an emulsifier for 120 s to obtain emulsion B.

[0052] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.05 g of ammonium persulfate and 0.06 g of calcium chloride were added under stirring, and 2 g of distilled water and 0.5 g of organosiloxane containing Si-N bonds were quickly added dropwise. After stirring for 20 min, 45.0 g of solution A obtained in step (1) was added dropwise to the three-necked round-bottom flask, and then 0.05 g of ammonium persulfate, 0.06 g of calcium chloride, 2 g of distilled water and 0.5 g of organosiloxane containing Si-N bonds were added to the three-necked round-bottom flask. After stirring for 40 min, solution C was obtained. The structure of the organosiloxane containing Si-N bonds is as follows:

[0053]

[0054] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant.

[0055] Example 4

[0056] The ammonium polyphosphate microcapsule flame retardant of the present embodiment is prepared by a method comprising the following steps:

[0057] (1) 7.0 g of boric acid, 15.0 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and placed in a 30° C. water bath. The pH of the material in the flask was then adjusted to 3 with glacial acetic acid. The material in the flask was stirred for 14 h. The material in the flask was then heated to 90° C., and a condenser was added and stirred for 9 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0058] (2) 10.0 g of ammonium polyphosphate, 1.5 g of emulsifier OP-20, 8.0 g of vinyltrimethoxysilane and 70 g of distilled water were added to a beaker and emulsified in an emulsifier for 30 seconds to obtain emulsion B.

[0059] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.2 g of potassium persulfate, 0.12 g of lithium chloride, 3.0 g of organosiloxane containing Si-N bonds, and 55.0 g of solution A obtained in step (1) were added under stirring conditions, and stirred for 50 min to obtain solution C. The structure of the organosiloxane containing Si-N bonds is as follows:

[0060]

[0061] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant.

[0062] Example 5

[0063] The ammonium polyphosphate microcapsule flame retardant of the present embodiment is prepared by a method comprising the following steps:

[0064] (1) 6.2 g of boric acid, 14.3 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and placed in a 30° C. water bath. The pH of the material in the flask was then adjusted to 3 with glacial acetic acid. The material in the flask was stirred for 12 h. The material in the flask was then heated to 90° C., and a condenser was added and stirred for 5 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0065] (2) 8 g of ammonium polyphosphate, 0.94 g of emulsifier OP-20 and 70 g of distilled water were added to a beaker and emulsified in an emulsifier for 30 seconds to obtain emulsion B.

[0066] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.2 g of sodium persulfate, 0.12 g of lithium chloride, 3 g of an organosiloxane containing a Si-N bond, 7.5 g of γ-acryloxypropyltriethoxysilane, and 50 g of the solution A obtained in step (1) were added under stirring, and stirred for 55 min to obtain a solution C. The structure of the organosiloxane containing a Si-N bond is as follows:

[0067]

[0068] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant.

[0069] Example 6

[0070] The ammonium polyphosphate microcapsule flame retardant of the present embodiment is prepared by a method comprising the following steps:

[0071] (1) 6.2 g of boric acid, 14.3 g of vinyltrimethoxysilane, 65 g of ethanol and 130 g of distilled water were added to a 500 mL three-necked round-bottom flask, and placed in a 30° C. water bath. The pH of the material in the flask was then adjusted to 4 with glacial acetic acid. The material in the flask was stirred for 14 h. The material in the flask was then heated to 95° C., and a condenser was added and stirred for 9 h to obtain a solution A containing a borosiloxane polymerization monomer.

[0072] (2) 8 g of ammonium polyphosphate, 1.5 g of emulsifier OP-20, 7.45 g of γ-methacryloxypropyltrimethoxysilane and 60 g of distilled water were added to a beaker and emulsified in an emulsifier for 30 seconds to obtain emulsion B.

[0073] (3) The emulsion B obtained in step (2) was placed in a three-necked round-bottom flask, and 0.1 g of ammonium persulfate and 1.5 g of an organosiloxane containing Si-N bonds were added under stirring. After stirring for 20 min, 50 g of the solution A obtained in step (1) was added dropwise to the three-necked round-bottom flask, and then 0.2 g of ammonium persulfate and 1.5 g of an organosiloxane containing Si-N bonds were added to the three-necked round-bottom flask. After stirring for 60 min, a solution C was obtained. The structure of the organosiloxane containing Si-N bonds is as follows:

[0074]

[0075] (4) The solution C obtained in step (3) was placed in an oven at 75° C. and dried for 12 h. After drying, the solution was ground to a particle size of 0.2 to 1 μm to obtain an ammonium polyphosphate microcapsule flame retardant.

[0076] Experimental Example 1

[0077] This experimental example characterizes the appearance and structure of the ammonium polyphosphate microcapsule flame retardant prepared in Examples 1-6. The SEM electron microscope image of the ammonium polyphosphate microcapsule flame retardant prepared in Example 1 is as follows: Figure 3 As shown, the infrared test picture is as follows Figure 4 The water contact angle test results are shown in Figure 5 shown.

[0078] from Figure 3 It can be seen that the surface of ammonium polyphosphate (APP) is very smooth and flat, while the surface of the ammonium polyphosphate microcapsule flame retardant modified by borosilicate polymerization monomer microencapsulation has many small balls, and a layer of small balls can be observed. The surface morphology is obviously very different from APP. It is precisely because of the existence of this layer of dense small balls that the coated and modified ammonium polyphosphate microcapsule flame retardant has strong hydrophobicity.

[0079] Figure 4 The infrared spectra of ammonium polyphosphate and ammonium polyphosphate microencapsulated flame retardant. -1 and 1244cm -1 is the stretching vibration of ammonium polyphosphate PO and P=O, 3421cm -1 The multiple peaks at 1007cm are the stretching vibration peaks of the free amino ion NH of ammonium polyphosphate. Since the free amino ion is relatively complex, it presents multiple peaks. -1 and 1442cm -1is the stretching vibration peak of PO and P=O of ammonium polyphosphate microencapsulation, 1119cm -1 The peak at 1726 cm is the CO stretching vibration peak of organosiloxane containing Si-N bonds. -1 The peak at 3520 cm is the C=O stretching vibration peak of the vinyl silane coupling agent. -1 The peak at is the stretching vibration peak of NH in ammonium polyphosphate microencapsulation. The absorption peaks at PO and NH in ammonium polyphosphate microencapsulation are smaller than those of ammonium polyphosphate. This is because the ammonium polyphosphate is encapsulated and the free amino ions are fixed, resulting in a weakened absorption peak intensity, which is consistent with the results of scanning electron microscopy, proving that the encapsulation of ammonium polyphosphate is relatively successful.

[0080] from Figure 5 It can be seen that the water contact angle test results show that the water contact angle of ammonium polyphosphate (APP) is 66.963 degrees, and the water contact angle of ammonium polyphosphate microcapsule flame retardant is 101.67 degrees. The increase in water contact angle indicates improved water resistance.

[0081] Experimental Example 2

[0082] In this experimental example, pure ammonium polyphosphate and the ammonium polyphosphate microcapsule flame retardant prepared in Examples 1-6 were used to prepare silicone rubber to test its flame retardant properties. The preparation method of silicone rubber comprises the following steps: (1) putting 30g of methyl vinyl silicone rubber into an internal mixer, and mixing at a speed of 20rpm for 2min, then mixing 2g of white carbon black powder, 17g of glass powder, and a certain amount of ammonium polyphosphate microcapsule flame retardant (the mass of ammonium polyphosphate microcapsule flame retardant is 3g, 6g or 9g) evenly, adding the mixture into the internal mixer, and mixing at a speed of 40rpm for 7min, finally adding 1g of hydroxy silicone oil into the internal mixer, and mixing at a speed of 50rpm for 10min to obtain a mixed mixture; (2) adding the mixed mixture into a double-roll open mill, adding a vulcanizing agent (the vulcanizing agent is 0.1g of platinum catalyst or 0.65g of di-2-pentane vulcanizing agent or 0.65g of di-2-tetra-vulcanizing agent) under the condition that the double-roll temperature is 30-45°C, mixing for 15min, and then performing molding in a molding machine, the molding temperature is 120°C, and the time is 3min to obtain silicone rubber. Then, the silicone rubber was subjected to a combustion test according to the standard GB / T2408-1996. The combustion test pictures of the silicone rubber prepared under the conditions of the addition of the ammonium polyphosphate microcapsule flame retardant of Example 1 in amounts of 3g, 6g, and 9g respectively and the curing agent being 0.1g of platinum catalyst are shown in the following figure: Figure 6 As shown, Figure 6 The three pictures from left to right represent the use of ammonium polyphosphate microcapsule flame retardant in the addition amount from left to right, respectively, 3g, 6g, and 9g. Figure 6It can be seen that with the increase in the amount of ammonium polyphosphate microcapsule flame retardant added, the cracks caused by the combustion of silicone rubber are gradually reduced. Among them, after the silicone rubber with 9g of ammonium polyphosphate microcapsule flame retardant added is burned, basically no cracks can be seen, and the flame retardant effect is obvious.

[0083] In addition, the flame retardant performance of silicone rubber prepared with different flame retardants was evaluated. The flame retardant grade and limiting oxygen index of silicone rubber prepared under the conditions of 6g flame retardant addition and 0.1g platinum catalyst as vulcanizer are shown in Table 1. The flame retardant grade test standard is GB / T2408-1996, and the limiting oxygen index test standard is GB2406-80.

[0084] Table 1 Flame retardant grade and limiting oxygen index of silicone rubber prepared with different flame retardants

[0085] Flame retardants Flame retardant grade Limiting oxygen index Example 1 UL94 V-0 29.5 Example 2 UL94 V-0 30.1 Example 3 UL94 V-1 29.3 Example 4 UL94 V-0 30.8 Example 5 UL94 V-0 29.4 Example 6 UL94 V-0 29.7 Pure ammonium polyphosphate UL94 V-2 25.3

[0086] As can be seen from Table 1, from the flame retardancy level and limiting oxygen index, it can be seen that the flame retardancy level and limiting oxygen index of the ammonium polyphosphate microcapsule flame retardant are improved, and the limiting oxygen index of Example 4 can reach 30.8.

[0087] Experimental Example 3

[0088] In this experimental example, the ammonium polyphosphate microcapsule flame retardant prepared in Examples 1-6 was used to prepare polylactic acid to test its flame retardant properties. The preparation method of polylactic acid includes the following steps: (1) 40g of polylactic acid was placed in an internal mixer, and internally kneaded at a speed of 60rpm for 2min, and then 4g or 8g of ammonium polyphosphate microcapsule flame retardant was added to the internal mixer, and internally kneaded at a speed of 60rpm for 7min to obtain an internally kneaded mixture; (2) The internally kneaded mixture was molded in a molding machine at a molding temperature of 180°C for 5min to obtain polylactic acid. Then, the polylactic acid was subjected to a combustion test according to the standard GB / T2408-1996. The combustion test pictures of the polylactic acid prepared under the conditions of adding the ammonium polyphosphate microcapsule flame retardant of Example 1 in amounts of 4.0g and 8.0g respectively are shown in the figure. Figure 7 As shown, Figure 7 The two figures from left to right represent the addition amount of ammonium polyphosphate microcapsule flame retardant 4.0g and 8.0g respectively. Figure 7 It can be seen that with the increase of the amount of ammonium polyphosphate microcapsule flame retardant added, the dripping of polylactic acid can be obviously found to be reduced after the polylactic acid combustion test. Among them, after the polylactic acid with 8g of ammonium polyphosphate microcapsule flame retardant added is burned, basically no dripping can be seen. Moreover, with the increase of the amount of ammonium polyphosphate microcapsule flame retardant added, the combustion test smoke of the polylactic acid sample is reduced, and the flame retardant effect is obvious.

[0089] In addition, the flame retardant properties of polylactic acid prepared with different flame retardants were evaluated, and the flame retardant grade and limiting oxygen index of polylactic acid prepared with a flame retardant addition amount of 8.0 g are shown in Table 2. The flame retardant grade test standard is GB / T2408-1996, and the limiting oxygen index test standard is GB2406-80.

[0090] Table 2 Flame retardant grade and limiting oxygen index of polylactic acid prepared with different flame retardants

[0091] Flame retardants Flame retardant grade Limiting oxygen index Example 1 UL94 V-1 27.5 Example 2 UL94 V-0 28.8 Example 3 UL94 V-1 28.1 Example 4 UL94 V-0 29.3 Example 5 UL94 V-0 28.9 Example 6 UL94 V-0 29.8 Pure ammonium polyphosphate UL94 V-2 24.3

[0092] As can be seen from Table 2, from the flame retardant grade and limiting oxygen index, it can be seen that the flame retardant grade and limiting oxygen index of the ammonium polyphosphate microcapsule flame retardant are improved.

Claims

1. An ammonium polyphosphate microcapsule flame retardant, characterized in that: The method comprises the following steps: ammonium polyphosphate, an alkenyl silane coupling agent and a borosilicate polymerization monomer are subjected to an emulsion polymerization reaction under the action of an organosiloxane containing Si-N bonds / persulfate redox system; the borosilicate polymerization monomer is obtained by a condensation reaction of alkenyl trialkoxysilane and boric acid, wherein the mass ratio of alkenyl trialkoxysilane to boric acid is (14-15):(6-7); the structure of the organosiloxane containing Si-N bonds is as shown in formula I; In formula I, R is methyl or ethyl.

2. The ammonium polyphosphate microcapsule flame retardant according to claim 1, characterized in that: The alkenyl silane coupling agent is γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-acryloxypropyl trimethoxysilane or vinyl trimethoxysilane.

3. The ammonium polyphosphate microcapsule flame retardant according to claim 1, characterized in that: The mass ratio of the ammonium polyphosphate, the alkenyl silane coupling agent and the borosilicate polymerization monomer calculated as boric acid is (6-10):(6-8):(1.2-1.8).

4. The ammonium polyphosphate microcapsule flame retardant according to claim 1, characterized in that: A catalyst is also added into the emulsion polymerization reaction, and the catalyst is calcium chloride and / or lithium chloride.

5. The ammonium polyphosphate microcapsule flame retardant according to any one of claims 1 to 4, characterized in that: The preparation method of borosilicate polymerization monomer is as follows: alkenyltrialkoxysilane, boric acid, water and ethanol are mixed to obtain a mixed solution, the pH of the mixed solution is adjusted to 3-4, the mixed reaction is carried out for 10-14 hours, and then the temperature is increased to 75-95°C, and the mixed reaction is continued for 5-9 hours to obtain a borosilicate polymerization monomer solution.

6. The ammonium polyphosphate microcapsule flame retardant according to claim 5, characterized in that: The emulsion polymerization method comprises the following steps: mixing ammonium polyphosphate, an emulsifier and water to obtain an emulsion; then adding an alkenyl silane coupling agent, a borosilicate polymerization monomer solution, a redox system and a catalyst into the emulsion for a mixing reaction; or mixing ammonium polyphosphate, an alkenyl silane coupling agent, an emulsifier and water to obtain an emulsion; then adding a borosilicate polymerization monomer solution, a redox system and a catalyst into the emulsion for a mixing reaction; the catalyst is calcium chloride and / or lithium chloride.

7. The ammonium polyphosphate microcapsule flame retardant according to claim 6, characterized in that: The mass ratio of ammonium polyphosphate, alkenyl silane coupling agent, borosilicate polymerization monomer solution, redox system and catalyst is (6-10):(6-8):(45-55):(2-5.4):(0.1-0.6).

8. The ammonium polyphosphate microcapsule flame retardant according to claim 6, characterized in that: The mass ratio of ammonium polyphosphate, emulsifier and water is (6-10):(0.5-1.5):(55-75).

9. The ammonium polyphosphate microcapsule flame retardant according to any one of claims 1 to 4, characterized in that: The mass ratio of the organic siloxane containing Si-N bonds to the persulfate is (1.0-3):(0.1-0.4); the persulfate is ammonium persulfate, potassium persulfate or sodium persulfate.

10. The ammonium polyphosphate microcapsule flame retardant according to claim 6, characterized in that: The mass ratio of ammonium polyphosphate, alkenyl silane coupling agent, borosilicate polymerization monomer solution, redox system and catalyst is (6-10):(6-8):(45-55):(2-3.2):(0.1-0.6); the mass ratio of organosiloxane containing Si-N bond and persulfate is (1.5-3):(0.1-0.3).

Citation Information

Cited By

  • Thermoplastic polyarylene sulfide-based composite cable and preparation method thereof

    CN120441983A

  • Composite flame-retardant material with core-shell structure as well as preparation method and application of composite flame-retardant material

    CN121005959A